answersLogoWhite

0


Best Answer

No. 3a 12 plus a 6 is not a solution Of an equation.

User Avatar

Wiki User

โˆ™ 2014-08-22 04:52:04
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.79
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1510 Reviews

Add your answer:

Earn +20 pts
Q: 3a 12 plus a 6 Is a Solution Of The Equation?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Is 3a 12 plus a 6 a Equation?

Yes. 3a plus 12 plus 6 is an example of an Equation.


What is -2a plus 3a plus 5b?

What is the solution of -2a plus 3a plus 5b


Simplify a plus 3a-2 plus 3a?

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.


What is 3a plus 2 equals a-6?

It's a simple linear equation with 'a' as the variable.Here's how to find the solution:3a + 2 = a - 6Subtract '2' from each side of the equation:3a = a - 8Subtract 'a' from each side:2a = -8Divide each side by '2' :a = -4


How do you do this A x 3 a plus 12?

Simplifying a = 3a + 12 Reorder the terms: a = 12 + 3a Solving a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = 12 + 3a + -3a Combine like terms: a + -3a = -2a -2a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = 12 + 0 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6


If 6a plus 3b equals 2 and b 4 then what is the value of 3a?

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.


If 12 plus 1.5a equals 3a What is a?

12+1.5a = 3a 12 = 3a-1.5a 12 = 1.5a Divide both sides by 1.5 to find the value of a: a = 8


How can the factoring of the first equation help you factor the second equation 9x2 power 18x plus 8 9a2power 18ab plus 8b2power?

The first equation factors to (3x + 2)(3x + 4) The second equation factors to (3a + 2b)(3a + 4b)


What is the value of a in the equation 3a plus b 54 when b 9?

a = 15.


What is a plus 3a-2 plus 3a simplified?

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a


What is the solution to a equals 3a plus 4?

a = 3a + 4 0 = 2a + 4 2a = -4 a = -2


Is a plus 2a equals 3a equation or expression?

It is, in fact, an identity - which is an equation which is true for all values of the variable.

People also asked